Precursors of hemangioma. - Mazzotta, F.; Troccoli, T.; Pisani, V.; Colonna, V.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2008)
The precursors of hemangioma are lesions initially flat, ischemic and telangiectasic, scarcely growing in the first months and later on regressing within several months or years. Here are reported the clinical features of 58 cases of precursors observed in the period 1988-2007 and followed up for an average period of time of 4.5 years.